(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Supplies for building are getting more expensive every day. The two essential components of the concrete are pozzolanic material and crushed rock. These days, a lot of scientists are investigating building materials that could both raise and lower construction prices. It has been shown that using some industrial leftovers and agricultural residues as construction materials, particularly in underdeveloped countries, provide a number of real advantages. It was discovered that there is a lot of potential for using coconut shells to replace part of the aggregate used in concrete. The current work consists solely of a compilation of data related to GFRGC and earlier studies conducted by other academics. Millions of tonnes of glass waste are created annually.